A sustainable ecosystem: building a learning community to facilitate transdisciplinary collaboration in packaging development. Issue 1 (30th December 2022) - Mulder‐Nijkamp, Maaike; de Koeijer, Bjorn
Abstract : Sustainability‐related developments become a differentiating factor in development processes. An area with a strong focus on sustainability‐related issues is packaging. In current packaging development processes, stakeholders focus on solving sustainability issues within their own boundaries. However, the complexities surrounding circular packaging can only be overcome by transdisciplinary collaboration. 'Traditional' collaboration shows to be incapable of overcoming packaging‐specific complexities. Therefore, we launch Packalicious, a research initiative aiming to establish transdisciplinary innovation as a collaborative learning ecosystem. In the initial research phase, a core stakeholder group developed the framework in which Packalicious operates. In the second (current) phase, the developed Packalicious framework is tested and improved. This design iteration builds on a transdisciplinary group‐based case study, where real‐life packaging challenges are tackled by diverse stakeholders. In this paper, we define and measure the efficacy of collaborative learning within Packalicious by means of three innovation indicators. The first results indicate that the approach yields more diverse solutions, and a positive connotation with on‐the‐spot transdisciplinary collaboration. However, it also exposes the differences in discipline‐related language and jargon. This paper contributes to academic insights by the establishment of a self‐sustaining transdisciplinary learning ecosystem, and the ways in which this bridges gaps between disciplines and stakeholders.